The Healing Effects of Conditioned Medium Derived from Mesenchymal Stem Cells on Radiation-Induced Skin Wounds in Rats - Sun, JiaYang; Zhang, YunFeng; Song, XianJi; Zhu, Jiajing; Zhu, QingSan (Cell transplantation, 2019)
Radioactive dermatitis is caused by the exposure of skin and mucous membranes to radiation fields. The pathogenesis of radioactive dermatitis is complex and difficult to cure. Wharton’s jelly-derived mesenchymal stem cells (WJ-MSCs) may serve as a promising candidate for the therapy of cutaneous wounds. The aim of this study was to investigate whether a WJ-MSC-derived conditioned medium (MSC-CM) could be used to treat radiation-induced skin wounds in rats using a radiation-induced cutaneous injury model. The present study was designed to examine MSC-CM therapy in the recovery of radiation-induced skin wounds in vitro and in vivo. Firstly, we prepared the MSC-CM and tested the effects of the MSC-CM on human umbilical vein endothelial cell proliferation in vitro. After that, we used a β-ray beam to make skin wounds in rats and tested the effects of MSC-CM on cutaneous wound healing in vivo. Our results indicated that MSC-CM secreted factors that promoted HUVEC proliferation, regeneration of sebaceous glands, and angiogenesis. Importantly, MSC-CM promoted wound healing in excess of the positive control (epidermal growth factor), with no, or smaller, scar formation. In conclusion, MSC-CM significantly accelerated wound closure and enhanced the wound healing quality. MSC-CM has a beneficial therapeutic effect on radiation-induced cutaneous injury skin in rats and in this way MSC-CM may serve as a basis of a novel cell-free therapeutic approach for radiation dermatitis.